2020
DOI: 10.1167/tvst.9.7.44
|View full text |Cite
|
Sign up to set email alerts
|

Limbal Metabolic Support Reduces Peripheral Corneal Edema with Contact-Lens Wear

Abstract: To assess the influence of limbal metabolic support on corneal edema during scleral-lens (SL) and soft-contact-lens (SCL) wear for healthy lens wearers. Methods: A two-dimensional (2D) model of the cornea and sclera was designed on Comsol Multiphysics 5.4 along with SL and SCL architectures to mimic lens-wear induced hypoxia. The cornea is suffused with oxygen and metabolites from the limbus and aqueous humor. Air oxygen is supplied from and carbon dioxide is expelled to the atmosphere. Lens-oxygen permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 45 publications
(141 reference statements)
4
44
0
Order By: Relevance
“…It is important to mention that the oxygen permeability ( Dk value) of the lens is as high as a therapeutic lens and there is no need for additional support of oxygen or other materials as suggested in other papers [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that the oxygen permeability ( Dk value) of the lens is as high as a therapeutic lens and there is no need for additional support of oxygen or other materials as suggested in other papers [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the corneo-scleral anatomy are provided in Kim et al [33]. SL and SCL with embedments are referred to as ESL and ESCL, respectively.…”
Section: Lens Designmentioning
confidence: 99%
“…To provide direct comparison between mathematical and clinical analyses, Leung et al [15] utilized metabolic kinetics [31] and the hydration pump-leak mechanism of Maurice [32] to determine central corneal swelling associated with different hypoxic conditions caused by various types of soft-contact-lens (SCL) wear. Recently Kim et al [33] expanded this work to 2 dimensions (2D) to determine central-to-peripheral corneal swelling for SCL and scleral-lens (SL) wear. The metabolic-mathematical model revealed that limbal metabolic support significantly reduces mid-peripheral and peripheral corneal swelling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations